2012
DOI: 10.1088/0004-637x/753/1/7
|View full text |Cite
|
Sign up to set email alerts
|

THE M31 VELOCITY VECTOR. I.HUBBLE SPACE TELESCOPEPROPER-MOTION MEASUREMENTS

Abstract: We present the first proper-motion (PM) measurements for the galaxy M31. We obtained new V-band imaging data with the Hubble Space Telescope ACS/WFC and the WFC3/UVIS instruments of three fields: a spheroid field near the minor axis, an outer disk field along the major axis, and a field on the Giant Southern Stream. The data provide five to seven year time baselines with respect to pre-existing deep first-epoch observations of the same fields. We measure the positions of thousands of M31 stars and hundreds of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(193 citation statements)
references
References 34 publications
7
185
1
Order By: Relevance
“…The LG is dominated by two big spirals: the Milky Way (MW) and M31, the next most-luminous galaxy is M33 which is ∼ 10 times less massive than M31, followed by several dozen less luminous dwarf galaxies, up to a distance of ∼ 3Mpc. The velocity vector of M31, with a low tangential velocity is consistent with a head-on collision orbit toward the MW (Cox & Loeb 2008;van der Marel et al 2012b;Sohn et al 2012).…”
Section: Introductionmentioning
confidence: 60%
“…The LG is dominated by two big spirals: the Milky Way (MW) and M31, the next most-luminous galaxy is M33 which is ∼ 10 times less massive than M31, followed by several dozen less luminous dwarf galaxies, up to a distance of ∼ 3Mpc. The velocity vector of M31, with a low tangential velocity is consistent with a head-on collision orbit toward the MW (Cox & Loeb 2008;van der Marel et al 2012b;Sohn et al 2012).…”
Section: Introductionmentioning
confidence: 60%
“…The combination of these three programs provide deep, multi-epoch optical imaging of three fields in M31 (M31 Spheroid, M31 Disk, and M31 Stream). These observations were used to measure the PM of M31 (Sohn et al 2012), and during the course of this study, PM catalogs for individual stars in the three HST fields were created. D13 selected Milky Way halo star candidates in colormagnitude space, using photometry from Brown et al (2009) Figure 1 demonstrates how our initial sample from D13 evolved into the sample used in this analysis.…”
Section: Hst Imaging: Proper Motionsmentioning
confidence: 99%
“…Thus it is necessary to perform careful calibrations of PSF shapes, geometric distortions, charge-transfer efficiency, color effects, time variability in calibrations, etc. (e.g., Anderson & King 2000;Sohn et al 2012). When this is done, the systematics can be controlled to levels below the typical random errors.…”
Section: Van Der Marelmentioning
confidence: 99%
“…In these models, the Clouds were assumed to have been long-term MW satellites moving on near-circular orbits in a logarithmic potential (e.g., Gardiner & Noguchi 1996). By contrast, orbit calculations based on the HST PMs in a cosmologically motivated MW halo potential (Sohn et al 2012) and the observed M33 PM from water maser observations (Brunthaler et al 2005). The MW and M31 will collide in ∼ 4 Gyr, and they will fully merge in ∼ 6 Gyr.…”
Section: The Magellanic Cloudsmentioning
confidence: 99%